BEYOND TECHNOCRATIC DIGITAL GOVERNANCE: A PHILOSOPHICAL INQUIRY INTO KNOWLEDGE, POWER, AND VALUES IN EDUCATION - Euis Indrawati; Nuryati Nuryati; Masruroh Masruroh; M Aldrin fedriansyah; H.Akhmad Jonny Irawan; Masriah Masriah (Universitas Islam Negeri Mataram, 2026)
Digital technologies increasingly structure the governance of Education through data-driven systems, algorithmic decision-making, and platform-based infrastructures. While digital governance is widely promoted as a neutral and efficient solution to educational management challenges, it is often grounded in technocratic rationality that remains insufficiently examined. This study critically explores digital Education governance beyond instrumental and technical perspectives by employing a philosophy-of-science framework. Using a qualitative conceptual methodology grounded in critical literature analysis, the study examines digital governance through interconnected epistemological, ontological, and axiological dimensions. The analysis reveals that digital governance privileges data-based knowledge as authoritative, reconfigures Education as a measurable and governable system, and embeds normative commitments centered on efficiency, control, and performance. These dynamics reshape power relations within educational institutions and risk marginalizing human judgment, ethical responsibility, and relational dimensions of Education. The study contributes a novel integrative conceptual framework that positions digital governance as a socio-epistemic and value-laden practice rather than a neutral administrative tool. By foregrounding the philosophical assumptions underpinning data-driven governance, this article provides a critical foundation for reimagining digital governance as a reflective, human-centered, and ethically accountable practice. The findings have significant implications for Theory and policy, particularly in guiding the responsible development of digital governance frameworks aligned with the normative purposes of Education.